2015
DOI: 10.1016/j.ridd.2015.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Three physiological responses in fathers and non-fathers’ to vocalizations of typically developing infants and infants with Autism Spectrum Disorder

Abstract: Children with ASD, even before receiving a formal diagnosis, express atypical patterns of distress vocalizations (namely, episodes of crying). Their cries have higher fundamental frequencies, shorter inter-bout pauses, and fewer utterances. Cries of children with ASD are also perceived differently from other cries, and these perceptual differences may alter parent-infant interaction. This study assessed multiple physiological responses in fathers and non-fathers to atypical distress vocalizations (cries of chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 34 publications
2
13
0
Order By: Relevance
“…As crying can be considered one of many challenging situations parents experience in their daily life, it is possible that parents with a child with ASD have their own strategy to deal with crying, such as staying calmer (with higher IBI compared to that of parents of TD children in our study) to crying. This is also in line with the previous study in which adults with parenting experiences (fathers) were found to be calmer (higher IBI) than non-parents while listening to cries (Esposito et al, 2015). Interestingly, these differences and similarities were observed not only during the listening of ASD cry, but also TD cry.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…As crying can be considered one of many challenging situations parents experience in their daily life, it is possible that parents with a child with ASD have their own strategy to deal with crying, such as staying calmer (with higher IBI compared to that of parents of TD children in our study) to crying. This is also in line with the previous study in which adults with parenting experiences (fathers) were found to be calmer (higher IBI) than non-parents while listening to cries (Esposito et al, 2015). Interestingly, these differences and similarities were observed not only during the listening of ASD cry, but also TD cry.…”
Section: Discussionsupporting
confidence: 92%
“…This is also in line with a previous study in which fathers were found to be calmer than non-fathers while listening to cries (Esposito et al, 2015).…”
Section: Current Studysupporting
confidence: 93%
See 3 more Smart Citations